Flexible high-performance zinc negative electrode three-dimensional current collector and preparation method and application thereof

Through the method of chemical copper plating layer on the flexible three -dimensional base, the problems such as zinc negative pole branches crystal growth have been solved, and the cycle life and Kuron efficiency of zinc ion batteries have been significantly improved, and more efficient battery performance is achieved.

CN119381457APending Publication Date: 2025-01-28WUHAN TEXTILE UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411347209.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In practical applications, zinc negative electrodes have problems such as zinc dendrites, corrosion, hydrogen evolution and passivation, resulting in performance defects in battery capacity, magnification, Coulomb efficiency and cycle life, limiting the promotion and application of water-based zinc ion batteries.

Method used

The method of chemical plating is used to prepare a three -dimensional flexible zinc negative aggregate fluid with good electrical conductivity and inhibiting the growth of the chinetic crystal. This method includes sensitive treatment of flexible three -dimensional base, and then grows in situ for copper layers in a chemical -plated solution.

Benefits of technology

A significant reduction of the battery nuclear overpower, evenly the electric field, and improved the cycle service life and Kuron efficiency of the battery. Especially at the current density of 5mA, it can have a 10mV nuclear nuclear potential and a stable cycle of more than 800 laps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381457A_ABST
    Figure CN119381457A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a flexible high-performance zinc negative electrode three-dimensional current collector and a preparation method and application thereof. The flexible high-performance zinc negative electrode three-dimensional current collector comprises a flexible three-dimensional substrate and a copper layer which grows on the flexible three-dimensional substrate in situ in a chemical plating mode. The preparation method comprises the following steps: cleaning and sensitizing a flexible three-dimensional substrate to obtain an active substrate; and immersing the active substrate into a copper salt-containing chemical plating solution, stirring, adding a reducing agent, stirring to react for a period of time, taking out, cleaning and drying to obtain the flexible three-dimensional current collector. By adopting a chemical plating method, the three-dimensional flexible zinc negative electrode current collector which has good conductivity and can inhibit dendritic crystal growth is prepared by using the non-conductive flexible substrate, the nucleation overpotential of the battery can be remarkably reduced, the electric field can be homogenized, and the cycle service life of the battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a flexible high-performance zinc negative electrode three-dimensional current collector and a preparation method and application thereof. Background Art

[0002] While wearable devices continue to strengthen their own functions, they are also developing in the direction of lightness, speed, and high integration to meet people's needs for various usage environments. Therefore, in order to ensure that these devices can operate effectively for a long time, it is of utmost importance to develop wearable energy storage devices with high mechanical flexibility, high energy density, long service life, safety and stability to match them. Against this background, flexible aqueous zinc-ion batteries, as a new generation of energy storage devices, have become a research hotspot in the battery field in recent years due to their high safety, abundant reserves, and environmental protection. The metal zinc negative electrode has a capacity of up to 5855mAh·cm -3 Theoretical volume capacity and 820 mAh cm -3 Theoretical mass capacity, low redox potential (-0.76V vs standard hydrogen electrode, SHE), and low cost are advantages. Moreover, compared with lithium-ion batteries that usually use organic electrolyte systems, aqueous zinc-ion rechargeable batteries use highly safe aqueous electrolytes, which not only reduces costs and environmental pollution, but also has great application prospects in flexible wearable devices that usually need to be used close to the body. However, zinc negative electrodes have problems such as zinc dendrites, corrosion, hydrogen evolution, and passivation in practical applications, resulting in performance defects in battery capacity, rate, coulombic efficiency, and cycle life, which greatly limits the promotion and application of aqueous zinc-ion batteries.

[0003] Research shows that zinc dendrite growth, hydrogen evolution and corrosion / passivation are closely linked. The aggravation of one problem is likely to lead to the linkage aggravation of the other two. At the same time, improving one problem can also effectively control the occurrence of the other two reactions. The root cause of the zinc dendrite problem is the uneven distribution of the electric field on the surface of the zinc negative electrode. Zinc ions tend to gather in places where the electric field is densely distributed and obtain electrons to deposit as zinc metal, forming protrusions and aggravating the uneven electric field, causing further growth of dendrites. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a flexible, high-performance zinc negative electrode three-dimensional current collector and a preparation method and application thereof.

[0005] A flexible high-performance zinc negative electrode three-dimensional current collector of the present invention comprises a flexible three-dimensional substrate and a copper layer in-situ grown on the flexible three-dimensional substrate by chemical plating.

[0006] Furthermore, the flexible three-dimensional substrate is one of cotton cloth, carbon cloth, linen, synthetic fiber, and engineering plastic substrate.

[0007] A method for preparing the above-mentioned flexible high-performance zinc negative electrode three-dimensional current collector comprises the following steps:

[0008] S1, cleaning and drying the flexible three-dimensional substrate;

[0009] S2, immersing in an aqueous solution containing tin chloride and hydrochloric acid for sensitization treatment to obtain an active substrate;

[0010] S3, immersing the active substrate in a chemical plating solution containing copper salt, stirring and adding a reducing agent, stirring and reacting for a period of time, taking out, cleaning and drying, to obtain the flexible three-dimensional current collector.

[0011] Furthermore, the copper salt is one of copper sulfate and copper chloride.

[0012] Furthermore, the reducing agent is one of sodium hypophosphite, sodium borohydride and formaldehyde.

[0013] Furthermore, the chemical plating solution includes a copper salt, a complexing agent, sodium hydroxide and anhydrous sodium carbonate.

[0014] Furthermore, the complexing agent is one of sodium citrate and potassium sodium tartrate.

[0015] A zinc negative electrode comprises the above-mentioned flexible high-performance zinc negative electrode three-dimensional current collector.

[0016] A zinc-iodine full battery comprises the above-mentioned zinc negative electrode.

[0017] The present invention adopts a chemical plating method and uses a non-conductive flexible substrate to prepare a three-dimensional flexible zinc negative electrode current collector with good conductivity and the ability to inhibit dendrite growth. The battery's nucleation overpotential can be significantly reduced, the electric field can be homogenized, and the battery's cycle life and coulomb efficiency can be significantly improved. In particular, the battery can have a nucleation overpotential of 10 mV and a stable cycle of more than 800 cycles at a current density of 5 mA. Under the same conditions, the corresponding metal foil has a nucleation overpotential of 86 mV and a cycle life of less than 40 cycles.

[0018] The preparation process of the invention is simple and the cost is low, and the invention has great application potential in the field of flexible aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1a and Figure 1b The scanning electron microscope image (SEM) of the copper-plated cotton cloth of Example 1;

[0020] Figure 2 This is the xrd diagram of the copper-plated cotton cloth of Example 1;

[0021] Figure 3a and Figure 3b The value of Example 1 at 5 mA·cm -2 Current density, 5 mA·h cm -2 The first cycle polarization and Coulomb efficiency diagram of the asymmetric button cell below;

[0022] Figure 4 This is a conductivity test diagram comparing the copper-plated cotton cloth and the hydrophilic carbon cloth of Example 1;

[0023] Figure 5 The tensile stress-elongation test of the copper-plated cotton cloth of Example 1 and the control group of the original cotton cloth and the hydrophilic carbon cloth;

[0024] Figure 6a and Figure 6b The scanning electron microscope image (SEM) of the nickel-plated cotton cloth of Comparative Example 1;

[0025] Figure 7a and Figure 7b At 2 mA·cm -2 and 10 mA cm -2 Coulombic efficiency diagram of copper-coated cotton cloth / / zinc foil asymmetric battery at current density of;

[0026] Figure 8 The scanning electron microscope image (SEM) of the copper-plated cotton cloth during zinc deposition in Example 1;

[0027] Fig. 9 This is a CV test graph of an asymmetric button cell assembled from copper-plated cotton cloth and zinc foil prepared in Example 1;

[0028] Fig.10a and 10b The rate and long cycle test diagram of the asymmetric button cell assembled with copper-plated cotton cloth and zinc foil prepared in Example 1;

[0029] Fig.11 Coulombic efficiency diagram of nickel-plated cotton cloth / / zinc foil asymmetric battery at a current density of 5 mA. DETAILED DESCRIPTION

[0030] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0031] A method for preparing a flexible high-performance zinc negative electrode three-dimensional current collector, the specific steps are:

[0032] Step 1: The flexible substrate is ultrasonically cleaned in acetone, water, and ethanol for 5-30 minutes to remove surface impurities and contaminants. Afterwards, the flexible substrate is transferred to an empty beaker and kept in a drying oven at 30-100° C. for 6-12 hours to obtain a clean substrate.

[0033] Step 2: Cut a piece of flexible substrate of appropriate size and immerse it in 100ml aqueous solution containing 0.5-3g tin chloride (SnCl2) and 2-10ml 38% hydrochloric acid (HCl) for sensitization. Add 0.1-1g tin foil to the above solution, stir for 2-15min, wash the substrate with deionized water for 2-5 times, and soak it in 100ml aqueous solution containing 10-200mg palladium chloride (PdCl2) and 0.1-2ml38% hydrochloric acid for activation for 2-15min, then wash it with deionized water for 2-5 times, and dry it at 40-100℃ for 3-12h.

[0034] Step 3: Immerse the active substrate in 100 ml of chemical plating solution containing 0.2-5 g of metal salt, 1-8 g of stabilizer, 0.4-4 g of sodium hydroxide (NaOH), and 0.1-1 g of anhydrous sodium carbonate (NaCO3). Then add 0.5-4 g of reducing agent to the above solution and stir (or heat and stir) until it becomes colorless and transparent (1-8 h). Take out and dry to obtain a flexible three-dimensional current collector.

[0035] Example 1

[0036] A flexible high-performance zinc negative electrode three-dimensional current collector comprises a cotton cloth substrate and a Cu layer in-situ grown on the cotton cloth.

[0037] The preparation method of the copper-plated cotton cloth of the present invention is:

[0038] Step 1: Wash the cotton cloth in acetone, water and ethanol for 30 minutes by ultrasonic to remove surface impurities and contaminants. Then transfer the cotton cloth to an empty beaker and keep it in a drying oven at 60°C for 8 hours to obtain a clean cotton cloth.

[0039] Step 2: Cut a piece (5×5cm 2 Size) cotton cloth and immersed in 100mL aqueous solution containing 1.5g tin chloride (SnCl2) and 6ml 38% hydrochloric acid (HCl) for sensitization treatment. 400mg tin foil was added to the above solution, stirred for about 5min, washed with deionized water for three times, and immersed in an aqueous solution containing 0.01g palladium chloride (PdCl2) and 0.2mL 38% hydrochloric acid for activation for 5min, then washed with deionized water for 3 times, and dried at 80℃ for 12h.

[0040] Step 3: Immerse the active cotton fabric in 100mL of chemical copper plating solution containing 1g of copper sulfate (NiSO4·5H2O), 3g of potassium sodium tartrate (NaKC4H2O6·4H2O), 0.6g of sodium hydroxide (NaOH), and 0.15g of anhydrous sodium carbonate (NaCO3). Then add 2ml of formaldehyde (HCHO) solution to the above solution and stir until it becomes colorless and transparent (about 180min). Take out and wash the copper-plated cotton cloth (Cu@CT) 3 times with deionized water and dry it at 80℃ for 12h.

[0041] The copper-plated cotton cloth was examined by scanning electron microscopy (SEM) to examine the morphology of the current collector. Figure 1 clearly shows the dense copper layer grown on the cotton cloth.

[0042] The copper-plated cotton cloth prepared in Example 1 was subjected to XRD test to confirm the substances therein, such as Figure 2 As shown, the characteristic peaks of copper can be observed.

[0043] The copper-plated cotton cloth and zinc foil prepared in Example 1 were used to assemble an asymmetric button cell (the electrolyte was 2 mol / L ZnSO4). Keeping other conditions the same, copper foil was used to replace the copper-plated cotton cloth and zinc foil to form an asymmetric button cell as a control group. The experimental results are shown in Figure 2. Figure 3a and 3b As shown, the results show that at a current density of 5mA, the copper-plated cotton cloth / / zinc foil asymmetric battery can have a nucleation overpotential of 10mV and a stable cycle of more than 800 cycles, and the coulombic efficiency is close to 100%. Under the same conditions, the nucleation overpotential of copper foil / / zinc foil is 86mV, and the cycle life is less than 40 cycles.

[0044] The copper-plated cotton cloth prepared in Example 1 was tested for conductivity using an electrochemical workstation, and a hydrophilic carbon cloth with a three-dimensional structure under the same conditions was used as a control group. The experimental results are as follows: Figure 4 As shown, the results show that after chemical copper plating on cotton cloth, the cotton cloth does have excellent conductivity, and its conductivity is about 6 times that of hydrophilic carbon cloth.

[0045] The copper-plated cotton cloth prepared in Example 1 was subjected to a tensile stress-elongation test, and the original cotton cloth and the hydrophilic carbon cloth with the same three-dimensional structure under the same conditions were used as the control group. The experimental results are as follows: Figure 5 As shown, the results show that the order of the maximum stress and maximum elongation that can be sustained is copper-plated cotton cloth > original cotton cloth > hydrophilic carbon cloth, which means that the flexibility of cotton cloth is better than that of carbon cloth. After chemical copper plating, the cotton cloth not only has conductivity, but also greatly improves its flexibility.

[0046] The copper-plated cotton cloth and zinc foil prepared in Example 1 were assembled into an asymmetric button cell (the electrolyte was 2 mol / L ZnSO4), and other conditions were kept the same, and an asymmetric button cell composed of copper foil and zinc foil was used as a control group. Cyclic tests were carried out at different current densities and capacities.

[0047] The experimental results are as follows Figure 7a and Figure 7b As shown, the results show that at 2 mA cm -2 and 10 mA cm -2 At a current density of , the copper-coated cotton cloth / / zinc foil asymmetric battery can undergo stable cycles of more than 1000 and 200 cycles respectively. Under the same conditions, the cycle life of copper foil / / zinc foil is less than 40 cycles.

[0048] The copper-plated cotton cloth and zinc foil prepared in the above Example 1 were assembled into an asymmetric button cell (the electrolyte was 2 mol / L ZnSO4), and zinc deposition was performed for different times using a blue battery test system. The battery was then disassembled, and the copper-plated cotton cloth electrode with zinc deposited was rinsed with deionized water and ethanol and dried.

[0049] Scanning electron microscopy (SEM) was used to examine the morphology of the current collector after zinc deposition, such as Figure 8 The uniform deposition and growth process of zinc on copper-plated cotton cloth is clearly shown.

[0050] The copper-plated cotton cloth and zinc foil prepared in Example 1 above were assembled into an asymmetric button cell (the electrolyte was 2 mol / L ZnSO4), and zinc deposition was performed for different times using a blue battery test system. Then the battery was disassembled, and the copper-plated cotton cloth electrode with zinc deposition was rinsed with deionized water and ethanol and dried. Ketjen black was coated on the hydrophilic carbon cloth and loaded with iodine, and zinc-iodine button cells (the electrolyte was 2 mol / L ZnSO4) were formed with the copper-plated cotton cloth with zinc deposition. CV tests were performed using an electrochemical workstation, and rate and long cycle tests were performed using a blue system.

[0051] CV test results are as follows Fig. 9 As shown, the oxidation peak and the reduction peak are centrally symmetrical in height, and the peak area has almost no change after three cycles, indicating that there is almost no capacity decay, proving that the assembled zinc-iodine full battery has high reversibility during the charge and discharge process.

[0052] The results of rate and long cycle tests are as follows Fig.10a and 10bAs shown in the figure, the coulombic efficiency of the whole battery is almost 100% in both the rate test and the long cycle test, which shows the high reversibility of the charge and discharge process. In the rate test, the rate ranges from 1C to 10C, and the capacity decays to about 64% at 1C, and there is almost no capacity decay when returning to 1C, which shows that the battery has good rate performance. In the long cycle test, the life of the whole battery is close to 1000 cycles, and there is almost no capacity decay, which shows that the whole battery has very good cycle performance.

[0053] Comparative Example 1

[0054] A flexible high-performance zinc negative electrode three-dimensional current collector comprises a cotton cloth substrate and a Ni layer in-situ grown on the cotton cloth.

[0055] The preparation method of the nickel-plated cotton cloth of the present invention is:

[0056] Step 1: Wash the cotton cloth in acetone, water and ethanol for 30 minutes by ultrasonic to remove surface impurities and contaminants. Then transfer the cotton cloth to an empty beaker and keep it in a drying oven at 60°C for 8 hours to obtain a clean cotton cloth.

[0057] Step 2: Cut a piece (5×5cm 2 Size) cotton cloth and immersed in 100mL aqueous solution containing 1.5g tin chloride (SnCl2) and 6ml 38% hydrochloric acid (HCl) for sensitization treatment. 400mg tin foil was added to the above solution, stirred for about 5min, washed with deionized water for three times, and immersed in an aqueous solution containing 0.01g palladium chloride (PdCl2) and 0.2mL 38% hydrochloric acid for activation for 5min, then washed with deionized water for 3 times, and dried at 80℃ for 12h.

[0058] Step 3: Immerse the active cotton fabric in 100mL of chemical nickel plating solution containing 2g of nickel sulfate (NiSO4·7H2O), 1.8g of sodium hypophosphite (NaH2PO2), 1g of ammonium chloride (NH4Cl), and 1g of sodium citrate (Na3C6H5O7·2H2O). Then add 3ml of NH3·H2O to the above solution to adjust the pH, and stir until it is colorless and transparent (about 90min). Take out and wash the copper-plated cotton cloth with deionized water 3 times, and dry it at 80℃ for 12h.

[0059] The nickel-plated cotton cloth was examined for the morphology of the current collector using a scanning electron microscope (SEM). FIG6 clearly shows the dense nickel layer grown on the cotton cloth.

[0060] The nickel-plated cotton cloth and zinc foil prepared in the above comparative example 1 were assembled into an asymmetric button cell (the electrolyte was 2 mol / L ZnSO4), and the battery cycle capacity was tested using a blue power system.

[0061] The experimental results are as follows Fig.11 As shown, the results show that at a current density of 5 mA, the average coulombic efficiency of the nickel-plated cotton cloth / / zinc foil asymmetric battery is only close to 82%, and the cycle life is only 24 cycles, while the copper-plated cotton cloth under the same conditions has a coulombic efficiency of close to 100% and a cycle life of more than 800 cycles. Therefore, it is more appropriate to use copper-plated cotton cloth as the negative electrode current collector of aqueous zinc-ion batteries.

[0062] For matters not mentioned above, the prior art applies.

[0063] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible high-performance zinc negative electrode three-dimensional current collector, characterized in that: The invention comprises a flexible three-dimensional substrate and a copper layer in-situ grown on the flexible three-dimensional substrate by chemical plating.

2. A flexible high-performance zinc negative electrode three-dimensional current collector according to claim 1, characterized in that: The flexible three-dimensional substrate is one of cotton cloth, carbon cloth, linen cloth, synthetic fiber and engineering plastic substrate.

3. A method for preparing a flexible high-performance zinc negative electrode three-dimensional current collector as claimed in claim 1 or 2, characterized in that: The steps include: S1, cleaning and drying the flexible three-dimensional substrate; S2, immersing in an aqueous solution containing tin chloride and hydrochloric acid for sensitization treatment to obtain an active substrate; S3, immersing the active substrate in a chemical plating solution containing copper salt, stirring and adding a reducing agent, stirring and reacting for a period of time, taking out, cleaning and drying, to obtain the flexible three-dimensional current collector.

4. The preparation method according to claim 3, characterized in that: Copper salt is one of copper sulfate and copper chloride.

5. The preparation method according to claim 3, characterized in that: The reducing agent is one of sodium hypophosphite, sodium borohydride and formaldehyde.

6. The preparation method according to claim 3, characterized in that: The chemical plating solution includes a copper salt, a complexing agent, sodium hydroxide and anhydrous sodium carbonate.

7. The preparation method according to claim 6, characterized in that: The complexing agent is one of sodium citrate and potassium sodium tartrate.

8. A zinc negative electrode, characterized in that It comprises the flexible high-performance zinc negative electrode three-dimensional current collector as described in claim 1 or 2.

9. A zinc-iodine full battery, characterized in that: Comprising the zinc negative electrode as described in claim 8.

Citation Information

Patent Citations

  • Preparation method of electric-conducting polyimide fiber

    CN101446037A

  • Flexible current collector, electrode containing flexible current collector, and battery

    CN106898729A

  • Preparation method of zinc anode material of flexible zinc-air battery and preparation of zinc-air battery

    CN106935806A

  • Carbon material containing metal coating, preparation method thereof and application thereof

    CN109802121A

  • Preparation method of flexible zinc-air battery taking waste cloth as matrix

    CN110943267A